Awareness on Oral Manifestation of Sarcoidosis Among Dental Students - V. P, PATHMASHRI.; GANAPATHY, DHANRAJ; PANDURANGAN, KIRAN KUMAR; VELAYUDHAN, ASHOK (The journal of contemporary issues in business and government, 2020)
The aim is to understand and create awareness about the oral manifestation of sarcoidosis among the dental students. Sarcoidosis is a common multisystemic granulomatous disease. Sarcoidosis is an inflammatory disease characterized by formation of non-necrotizing epithelioid granulomas. Granulomas are tiny clumps of inflammatory cells in one or more organs in our body. These can interfere with an organ’s function and structure, if our immune system is over driven by these clumps of inflammatory cells. The commonly affected organ is lungs and in the head and neck its salivary glands. Oral manifestations of sarcoidosis are very rare and usually appear as non-tender swelling and ulcers in the lips, hard and soft palate, buccal mucosa, tongue and tonsils. The intraoral localized sarcoid lesion is histologically similar to a generalized sarcoidosis. No single test is enough for diagnosing and the presence of granuloma is also not enough to conclude the diagnosis. Oral manifestation of sarcoidosis is unusual, dentists must be aware that oral manifestation is specific localization and it is usually the first manifestation of the diseases. Therefore by knowing the oral manifestation of sarcoidosis, the dental students can be more aware of the prevalence of sarcoidosis and spread awareness among the patients.